Methodological bases for assessing the level of innovative development of agriculture and its service infrastructure activities - KHAMRAEVA, SAYYORA NASIMOVNA; ALIMOVA, MUNISA YULCHIYEVNA (The journal of contemporary issues in business and government, 2021)
The article examines methods for assessing the level of innovative development of agriculture and its ervice infrastructure sectors. In the process of development, the innovative development of the infrastructure that serves it is scientifically justified. Uzbekistan has developed a conceptual model for the formation and development of innovative infrastructure in the agricultural sector, taking into account the conditions and factors of innovation policy. The effectiveness of innovative infrastructure in agriculture is considered in terms of strategic, economic, and social effectiveness, from the point of view of state and territorial authorities, economic entities in agriculture, and entities receiving innovative infrastructure. The methodology for determining the impact of innovative development of agriculture and its service infrastructure on efficiency has also been improved.